Influence of endometrioma size on ART outcomes. Issue 6 (December 2022) - Bourdon, Mathilde; Dahan, Yaniv; Maignien, Chloé; Patrat, Catherine; Bordonne, Corinne; Marcellin, Louis; Chapron, Charles; Santulli, Pietro
Abstract: Research question: Does endometrioma size affect the number of oocytes retrieved after ovarian stimulation in women with endometriosis-related infertility undergoing IVF/intracytoplasmic sperm injection (ICSI)? Design: Cohort study of infertile women with unilateral or bilateral endometrioma(s) associated with deep infiltrating endometriosis, undergoing their first IVF/ICSI cycle between January 2014 and November 2021. A total of 326 women with an adequate imaging work-up with transvaginal ultrasound and/or magnetic resonance imaging performed by senior radiologists before the start of ovarian stimulation was included. Prognostic factors associated with the number of oocytes retrieved were analysed. IVF/ICSI outcomes were compared between five groups defined according to the largest endometrioma diameter (<2, 2 to <4, 4 to <6, 6 to <8 and ≥8 cm). Results: Factors that significantly reduced the number of oocytes retrieved after adjustment by multiple linear regression were women's age (regression coefficient –0.18; 95% confidence interval [95% CI] –0.31 to–0.06; P  = 0.005), smoking habit (–2.02; 95% CI –3.42 to -0.62; P  = 0.005), day 3 FSH concentration (–0.20; 95% CI –0.39 to –0.02; P  = 0.031) and a previous history of surgery for ovarian endometriosis (–1.32; 95% CI –2.63 to –0.02; P  = 0.047). Antral follicle count and oestradiol concentration on the trigger day were positively correlated with the number of oocytes retrieved (0.14; 95% CI 0.08 to 0.19; P < 0.001 and 0.003; 95% CI 0.002 to 0.004; P < 0.001, respectively). The mean number of oocytes retrieved was not significantly different between the five groups ( P  = 0.413), nor were the cumulative live birth rate, the number of cancelled cycles and perinatal outcomes. Conclusions: No significant difference in the number of oocytes retrieved was observed according to endometrioma size. This study suggests that ovarian stimulation can be of benefit to women irrespective of the endometrioma size.